Effects of partial replacement of soybean meal with hemp seed (Cannabis sativa L.) cake on the growth and meat quality in female three-yellow chickens - Qin He; Zongyao Zhang; Hao Tian; Haopeng Wang; Xiaoyu Lu; Hexuan Deng; Fujian Yang; Xuemei Tang; Jian Wang; Zhipeng Li; Hui Li; Shuibao Shen; et al. (Poultry Science)
Hemp seed cake (HSC) (Cannabis sativa L.) is a high-quality plant-derived protein source rich in polyunsaturated fatty acid (PUFA). To assess the effects of HSC addition in diets on the growth and meat quality in broiler chicken, a total of 240 female three-yellow chickens (50 days of age) were randomly assigned to four groups and fed with varying levels of HSC (0% (HSC0), 5% (HSC5), 10% (HSC10), and 20% (HSC20)) for 9 weeks. As a result, the daily feed intake, weight gain and feed conversion efficiency were significantly increased in the HSC20 group. Moreover, the meat quality traits, including the meat colour, water-holding capacity, intramuscular fat content, and proportion of n-3 PUFA significantly improved, and the expression of lipid synthesis genes, were increased in the HSC20 group. Meanwhile, the development of immune organs and the anti-inflammatory capabilities were enhanced in the HSC20 group. In addition, the blood lipid of chicken was reduced by improving the lipid metabolism in the HSC20 group. Therefore, adding 20% HSC in the feed had a notable effect on the growth, antioxidant and immune capabilities, blood lipid metabolism, and meat performance of the female three-yellow chickens. These findings provide significant information for improving the production performance of broiler chickens through the effective utilization of HSC.